Traces of Religious Moderation in the Tafsir of the Qur'anuladhimi by Hasan Mustopa - Gusti Rahma Sari S; Gery Giovano; Irfan Fadlurrahman (Gunung Djati Conference Series, 2021)
Religious moderation is a policy goal of the Ministry of Religion because of the various acts of terrorism that have occurred and the Covid-19 pandemic situation. Therefore this paper examines how religious moderation is in Hasan Mustopa's interpretation of the Qur'anuladhimi. The choice of the Qur’anuladhimi is because there is an aspect of tolerance in the interpretation. This research is a type of qualitative research through literature study with content analysis techniques. The results of this study indicate that in Hasan Mustopa's interpretation of Surah Al-Baqarah verses 143 and 256 there are values of religious moderation. These values are i'tidal (straight), tawasuth (taking the middle way), tawazun (balance), and tasamuh (tolerance). This study only analyzes two verses of religious moderation in Hasan Mustopa's interpretation. This study recommends looking for and examining other verses related to religious moderation in the Qur'anic interpretation.